Rewriting Magic : An Exegesis of the Visionary Autobiography of a Fourteenth-Century French Monk - Fanger, Claire (Magic in history., 2015)
"Examines the text and background of The Flowers of Heavenly Teaching, an autobiography by the fourteenth-century Benedictine monk John of Morigny. Explores how the author negotiated the categories of magic and heresy in relation to Christianity"--Provided by publisher.